Froylán Turcios (1874-1943) and Modernism in Central America - Funes, José Antonio (Anales de Literatura Hispanoamericana, 2006)
Honduran Modernist Froylán Turcios was one of the most educated and informed writers of his time. He was known as a director of magazines, an organiser of cultural events, a journalist and a diplomat. In a Honduran context, he stands out as a poet alongside Juan Ramón Molina (1875-1908), whom he accompanied to the Third Pan-American Conference which was held in Río de Janeiro in 1906. It was there that these two Hondurans met Rubén Darío, in what was to be the beginning of a close friendship. The article also considers Turcios’ relations with other Central American writers, some of them forgotten, but all of them important figures in the Modernism of the region: Rafael Ángel Troyo, from Costa Rica; Arturo Ambrogi, from Salvador; Rafael Arévalo Martínez, from Guatemala.
Keywords: Froylán Turcios